Study of Waiting Times and Outpatient Visit Rates for BPJS and Non BPJS Patients at the East Kalimantan Provincial Eye Hospital - Sinar Sinar; Ratno Adrianto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hospital service waiting time is the time required from the time a patient registers until they are served by a specialist. The minimum outpatient waiting time standard is ≤ 60 minutes, but most patients exceed it. This long waiting time can result in decreased patient satisfaction and the risk of a decrease in the number of visitors. Objective : The aim to determine the waiting time for services and the number of visits by BPJS and non-BPJS participants at the East Kalimantan Provincial Eye Hospital. Research Methods/ Implementation Methods : This study was descriptive, with data sources from the Eye Hospital Information System. Analysis is carried out by presenting tables, graphs, and in- depth explanations. Results : Most patient service waiting times were more than 60 minutes, with a percentage ranging from 45.9% to 85.2%. From February to April 2025, there was an increase, then a decrease, and then an increase again in August 2025. In August 2025, the waiting time was the highest, with 1,883 people (85.2%). And the highest number of visits occurred in July 2025, with 2,514 people, comprising 2,319 (88.71%) BPJS participants and 295 (11.29%) non-BPJS patients. Conclusion/Lesson Learned : that patient waiting times exceeding 60 minutes were recorded for 75.3% of BPJS participants, while the average for non-BPJS patients was 55.3%. Meanwhile, patient visits from January to August 2025 increased by 2021.9 per month.